Is the formalization of collective tenure rights in the Peruvian Amazon supporting sustainable Indigenous livelihoods? Findings from comparative research in San Martín and Ucayali regions - Guerra, Miguel; Sarmiento Barletti, Juan Pablo; Begert, Blanca (Center for International Forestry Research, 2021)
Key findings The titling of Comunidades Nativas (Native Communities) alone is not enough to ensure Indigenous Peoples’ access to sustainable livelihoods in the Peruvian Amazon. Lack of income options, combined with restrictive legal frameworks for resource use under the Comunidad model, led to unsustainable land and resource use. In seeking to access cash incomes, Comunidades often entered into exploitative relationships with smallholder migrant farmers and timber companies. Regulations for resource use and the Comunidad’s governance framework do not reflect local livelihoods and leadership practices; interviewees highlighted that this created challenges related to livelihoods, conflicts, participation and representation in communal governance. A transition from a punitive to an enabling role for government agencies – including investing to develop both the institutional and technical capacities of Comunidades – is essential to support more sustainable livelihoods.